Bridges of Peace: The Role of Symbols and Rituals in Peacebuilding - Mahmuluddin, Mahmuluddin (Journal of Contemporary Rituals and Traditions, 2024)
Purpose of the Study: This article investigates how symbols and rituals contribute to conflict management in deeply divided societies. Methodology: Through qualitative library research, this study examines the impact of symbols and rituals on peace-building by analyzing theoretical frameworks and case studies. Main Findings: The study identifies that symbols and rituals play a crucial role in the peace-building process, achievable through two primary methods: the creation of new symbols and rituals that draw on inclusive narratives to foster a shared symbolic space promoting multicultural tolerance, and the creative manipulation of existing symbols and rituals to challenge and subvert historical power dynamics. Applications of this Study: The findings offer valuable insights for policymakers, peace-building practitioners, and community leaders engaged in conflict resolution and reconciliation efforts. By understanding the dual potential of symbols and rituals in peace-building, stakeholders can develop more effective strategies to address the underlying causes of division and promote enduring peace in divided societies.  Novelty/Originality of this Study: This research contributes to the field by providing a comprehensive analysis of the transformative power of symbols and rituals in peace-building. It showcases how these cultural elements can be strategically leveraged to support reconciliation and unity, marking a significant advancement in the understanding of non-traditional mechanisms of conflict resolution and peace-building efforts.